A business model analysis of Kmart's downfall. Issue 2 (16th April 2019) - Brea-Solís, Humberto A.; Grifell-Tatjé, Emili
Abstract : Purpose: The purpose of this paper is to understand how a major retailer like Kmart lost its dominant position in the American retail industry. Design/methodology/approach: This paper contains a decomposition of profit change into meaningful economic drivers using a methodology that combines frontier analysis with index number theory. The empirical analysis is complemented with a description of Kmart's business model produced from corporate documents and other sources. Findings: A quantification of Kmart's business model performance expressed in monetary terms. This assessment is presented by CEO tenures showing the contribution of different economic drivers to the evolution of profits. Practical implications: The study's empirical results highlight the importance of the correct implementation of all aspects of the business model in order to achieve success. Originality/value: This paper presents a new empirical framework to assess business model performance. Despite Kmart's important role in American discount retailing history there have been very few studies that have analyzed its downfall. This paper contributes by filling that gap.